Individual strategies in the tasks of graphical retrieval of technical drawings. (June 2015) - Kasimov, Denis R.; Kuchuganov, Aleksandr V.; Kuchuganov, Valeriy N.
Abstract: A designer׳s information need can have a lot of finer points not expressible completely by textual attributes or global aggregated image features. The purpose of the study is to develop a cognitive environment for content-based engineering drawing retrieval, allowing a user to concretize queries, to implement strategies that are most effective for the current search task. We propose meaningful customizable graphic search patterns, various comparison modes and visualization of matched elements. The presented experiments show that the approach yields good results in the sense of relevance and is comfortable in terms of controllability. The possibility to customize search patterns can result in improving retrieval precision by 10–15%. In practice, it can significantly increase the degree of automation of the design-reuse process. Highlights: A cognitive environment for content-based technical drawing retrieval is proposed. It provides various meaningful graphic search patterns. Customization of search patterns is an effective way of query concretization. The retrieval system satisfies designers by relevance, transparency, control, and guidance. The environment allows a user to implement flexible search strategies.